UPAYA INDONESIA MENINGKATKAN JUMLAH KUNJUNGAN WISATAWAN MANCANEGARA DI KEPULAUAN RIAU - Karlina, Tika; Iskandar, Irwan (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2017)
This study aims to know Indonesian government tourism policy to develop tourism sector in Riau Island and to know the efforts of the Indonesian government to increase the visit of foreign tourists in Riau Island.The method of the research that was used is descriptive qualitative, to describe the phenomena in real situation without make comparing or answering hypothesis. The analysis is based on data obtained either from the literature studies and field studies, that is by conducting direct-interview with informants who are considered capable to provide information related the problem under study.The results of the research are the number of tourists increased since 2013. Increased visits of foreign tourists are influenced by the policy of the central government and regional governments that are mutually sustainable. Another factor is the availability of attractive tourist objects and accessible infrastructure.Keywords: Tourism, Foreign Tourist, Government Policy